Pengaruh Kualitas Pelayanan Publik dan Citra Institusi terhadap Kepuasan Mahasiswa Ilmu Komunikasi UIN Sumatera Utara yang Berdampak pada Word of Mouth - Afwan Syahril Manurung; Syafruddin Pohan (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2024)
This research aims to examine the influence of public service quality and institutional image on student satisfaction, as well as its impact on student word of mouth at UIN North Sumatra. We used probability sampling techniques with proportional stratified random sampling, with 80 respondents. Data analysis was carried out using path analysis. The research results show that service quality has a positive effect on student satisfaction. Likewise, a strong institutional image also increases student satisfaction. In addition, an indirect influence was found between service quality and institutional image on student satisfaction through institutional image and service quality respectively. There is also a simultaneous influence between service quality and institutional image on student satisfaction. The better the quality of service and image of the institution, the higher student satisfaction. Student satisfaction has a positive impact on word of mouth. The implications of this research suggest improvements in service quality and institutional image to increase student satisfaction. This is important to increase marketing through word of mouth as an effective communication and marketing medium in facing increasingly fierce higher education competition.